Mindfulness in Communication, Tolerance, and Harmony in Buddhist Community Living: A Study of Religious Moderation on Education and Communication - Ivana Pramita; Vike Aprilianin Marwintaria Saputri; Sandjaja Dharmatanna; Wistina Seneru; Sidartha Adi Gautama; Burmansah Burmansah; Mega Julianti (Universitas Sebelas Maret, 2024)
This study examines the influence of mindfulness in communication on tolerance and harmony among Buddhists at Wihara Dipa Prabhava. Using a survey method with a sample of 112 respondents, the research found that the application of mindfulness-based communication significantly enhances tolerance and harmony among individuals. These findings emphasize the importance of mindfulness in fostering harmonious communication and reducing conflicts within the Buddhist community. The results indicate a significant positive effect of mindfulness in communication on tolerance and harmony among Buddhists, with a t-value of 10.729, a significance value (p) of 0.000 < 0.05, And an R Square value of 0.511 obtained from the simple regression analysis. This means that mindfulness in communication influences tolerance and harmony by 51.1%, while other factors affect the remaining 48.9%.